Membina perisian multimedia mengenai Fiqh al-muamalah untuk tahap kolej / Sazalinsyah Razali - Razali, Sazalinsyah (2000)
Currently, there are not many references on Fiqh Al-Muamalah available for college students. Thus, the objectives of this thesis are to provide an alternative multimedia software on Islamic Fiqh and to make the study of Fiqh Al-Muamalah more interesting by offering an interactive application. This project uses the waterfall model, which comprises of five different phases, that are, problem analysis, package design, software implementation, package testing and documentation, and maintenance. This thesis only focuses on the four sub-sections of Fiqh Al-Muamalah, which are Al-Bai', Al-Khiyar, Prohibited Transactions, and Al-Riba. The target age group for this multimedia product is between 18 to 35 years old. The product's scope includes quizzes and analysis of the results obtained by users. This study's conclusions indicates that by gathering all of the Islamic Rulings regarding Al-Muamalah in a multimedia package makes learning this subject more understandable and effective.